(3RgQ GdQjGV aj QO eGTfYg GdbGVi YjGV Ydi ef ChLH GdUdGI Ydi GdHTjQ GdfPjQ aj GdJTgOs - (3CHh YHO Gddg eMeO Hf eMeO Hf YHO Gddg Hf NVjQ GdNjVQj GdTGaYj,J (B894 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eXgQ GdMb heYdjg CeG HYO aEf de CNd ai ZGdH ChbGJ ef GdfXQ hGdJMQjQ hef LedI GdcJH GdJi CeYfJ GdfXQ ajgG cJGH GdTaG s
(3BNQgG (B:s
(3BNQ cJGH RgQ GdQjGV s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B30s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCMbGa eLehYg Bd jMi (B(191) s
Keywords: (3GNJdGa GdabgGAs